(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2015)
review of The crucible of resistance: Greece, the Eurozone & the world economic crisis. Christos Laskos and Euclid Tsakalotos. London: Pluto Press. 2013. After neoliberalism? The Kilburn manifesto. Stuart Hall, Doreen Massey and Michael Rustin (eds.). London: Lawrence and Wishart Ltd. 2015.